Modeling which factors impact interest rates - Guizhou Wang; Kjell Hausken (Journal of Central Banking Theory and Practice, 2023)
The Taylor (1993) rule for determining interest rates is generalized to account for three additional variables: The money supply, money velocity, and the unemployment rate. Thus, five parameters, i.e. weights assigned to the deviation in the inflation rate, the deviation in real GDP (Gross Domestic Product), the deviation in money supply, the deviation in the money velocity, and the deviation in unemployment rate, are introduced and estimated. The article explores and tests various combinations of the Taylor rule, the Quantity Equation (Friedman, 1970), and the Phillips (1958) curve. The monthly US January 1, 1959 to March 31, 2022 data are adopted to test the optimal parameter values. Estimating the parameters with the least squares method gives better results than the Taylor rule. The optimal parameter values involve a relatively high weight to the deviation in unemployment rate, and moderate weights are assigned to the deviation in the inflation rate, the deviation in real GDP, the deviation in money supply, and the deviation in the money velocity. The corresponding sum of squares decreases by 42.95% when compared with the Taylor rule.
Keywords: C6; E24; E50; E47; E52; E58; 330; Monetary policy; Taylor rule; Quantity Equation; Phillips curve; interest rates; inflation rate; GDP; money supply; moneyvelocity; unemployment rate